Menanam Jiwa Kepemimpinan Kristen Sejak Remaja di Era Digital - Safira Supriani Jangga Ndewa; Melisa Melomfia Lestari; Semuel Linggi Topayung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Instilling a Christian leadership spirit since adolescence can have a very important influence on the Christian environment or life both in non-Christian environments Christian leadership can also shape a person’s individual character and instill Christian values in the surrounding environment, thus providing a good example for fellow christians both in non-Christian enviroments Christians leadership is not only about how potential leaders can lead others but must also be able to lead themselves in today’s digital era this article discusses the improtance of instilling a christian leadership spirit since adolescence in the current digital era through a holistic approach, so that each individual can lead themselves before leading others and can provide Khristian values in everyday life the method used in this study is a literature study that examines literature in the process of colleting opinions from various literature analyses of other sources that are in accordanc with the topic of research of study from the study show that instilling a Christian leadership spirit can be applied through our spiritual actibities, our spiritual awakening such as prayer, worship or other fellowship in conclusion, instilling a Christians leadership since adolescence in the current digital era can help someone to shape their character and can bring themselves to be an example of Christ for their environment.